Preparation of Fe-intercalated Graphite Based on Coal Tailings, Dimensional Structure - Irfan Gustian; Eka Angasa; Dwi Agustini; Evi Maryanti; Dyiah Fitriani (Aceh International Journal of Science and Technology, 2015)
Intercalated graphite from coal tailings have been modified through the intercalation of iron. Coal tailings which is a byproduct of the destruction process and flakes washing results from mining coal. Intercalation of iron goal is to improve the physical properties of graphite and modifying sizes of crystal lattice structure with thermal method. Modification process begins with the carbonization of coal tailings at 500ºC and activated with phosphoric acid. Activation process has done by pyrolysis at 700ºC. The results of pyrolysis was soaked in mineral oil for 24 hours, then pyrolysis again with variations in temperature 800°C and 900ºC for 1 hour and subsequent intercalation iron at 1% and 2%. Material before activated, after activated, and the results of pyrolysis still indicates order nano: 29, 25 and 36 nm respectively. X-ray diffraction characterization results indicate that change in the structure, the sizes crystal lattice structure of the material The greater the concentration of iron was added, the resulting peak at 2θ = 33 and 35 also will be more sharply. The results of SEM showed different morphologies from each treatment.